Suitability of a Minipig Model in Assessing Clinical Bioperformance of Matrix and Multiparticulate Extended‐Release Formulations for a BCS Class III Drug Development Candidate. Issue 2 (30th December 2013) - Kesisoglou, Filippos; Xie, Iris Huizhi; Manser, Kimberly; Wu, Yunhui; Hardy, Ian; Fitzpatrick, Shaun
<x xml:space="preserve">Abstract</x> Preclinical studies in dogs are often employed as part of formulation screening process. However, the shorter transit time and colonic length in dogs may result in underestimation of absorption, especially for extended‐release (ER) formulations. In the recent years, minipigs have attracted attention as an alternative animal model. However reports on studies with ER formulations are limited. In this manuscript, we report the first comprehensive comparison of minipig and clinical data for two types of ER formulations. Matrix tablets and multiparticulates in capsules of a BCS Class III compound were tested in the Yucatan minipig model. The relative performance of the formulations in minipigs in the fasted state was reasonably aligned with the clinical observations. The minipig model was able to rank order the formulations, reflecting the targeted release rate, in a manner consistent with the clinical data. Minipigs also reflected the loss of bioavailability relative to the immediate‐release formulation. A level C in vitro/in vivo correlation was demonstrated for both the minipig and clinical data. However, an assessment of food effect in the minipig model appeared challenging, especially for the matrix formulation for which a negative food effect was observed in minipigs compared with the positive food effect in the clinic. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:636–642, 2014